(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article provides a scholarly analysis of the formation and development stages of the system for training economic specialists in Uzbekistan during the Soviet period, as well as its main characteristics. In addition, the activities of Tashkent State University of Economics (TSUE), its role and significance in training economic professionals, are examined based on historical and academic sources.